Ultrastructural changes of Fusobacterium nucleatum as a defense mechanism against human neutrophil peptide-1 - A Transmission Electron Microscopy (TEM) study - Fteita, Dareen (fi=Turun yliopisto|en=University of Turku|, 2015)
Aims: The aim of this work was to assess the ultrastructural changes, cellular proliferation, and the biofilm formation ability of F. nucleatum as defense mechanisms against the effect of HNP-1. Materials and methods: The type strain of F. nucleatum (ssp. nucleatum ATCC 25586) and two clinical strains (ssp. polymorphum AHN 9910 and ssp. nucleatum AHN 9508) were cultured and incubated with four different test concentrations of recombinant HNP-1 (1, 5, 10 and 20 µg/ml) and one control group (0 µg/ml). Bacterial pellets from each concentration were processed for TEM imaging. Planktonic growth was assessed and colony forming units (CFU) were measured to determine the cellular proliferation. Scrambled HNP-1 was used for confirmation. Results: TEM analyses revealed a decrease in the outer membrane surface corrugations and roughness of the strain AHN 9508 with increasing HNP-1 concentrations. In higher concentrations of HNP-1, the strain AHN 9910 showed thicker outer membranes with a number of associated rough vesicles attached to the outer surface. For ATCC 25586, the treated bacterial cells contained higher numbers of intracellular granules with increasing the peptide concentration. Planktonic growth of the two clinical strains were significantly enhanced (P<0.001) with gradually increased concentrations of HNP-1. None of the planktonic growth results of the 3 strains incubated with the scrambled HNP-1 was statistically significant. HNP-1 decreased the biofilm formation of the two clinical strains, AHN 9910 and 9508, significantly (P<0.01 and P<0.001; respectively). Conclusions: The present in vitro study demonstrates that F. nucleatum has the ability to withstand the lethal effects of HNP-1 even at concentrations simulating the diseased periodontium in vivo. The increase in planktonic growth could act as defense mechanisms of F. nucleatum against HNP-1.